Synthesis of doped MnOx/diatomite composites for catalyzing ozone decomposition. Issue 6 (15th April 2019) - Rao, Yi; Zeng, Debo; Cao, Xiaozhou; Qin, Gaowu; Li, Song
Abstract: The wide applications and unintended generation of ozone stimulate the exploration of catalysts for ozone decomposition. Herein, manganese oxides loaded on porous ceramic beads were prepared via a simple thermolysis method. Doping the composite with Ni, Fe, and Al could tune the oxygen vacancies in the manganese oxide, as evidenced by the X-ray photoelectron spectroscopy (XPS) analysis. The average valance of Mn could also be altered by the dopants. The catalytic properties of the composites doped with Fe, Ni, and Al have been significantly improved. And the Ni doped MnOx with the highest density of oxygen vacancy exhibits the best catalytic activity. The prepared composite catalyst can easily be incorporated into filters for air circulation.